The need to establish a national vascular surgery registry - Siddiqui, Mishal Shan; Khalid, Saad; Berlas, Fahad Tariq (Journal of the Pakistan Medical Association, 2022)
Madam, The integration of information technology (IT) in healthcare and data has resulted in significant medical research advancement. The International Consortium of Vascular Registries is one such example where registries from several countries contribute to the development in vascular surgery via cross-border collaborations.1 Similar successful examples from other fields include the Karachi Cancer registry and Pakistan National joint Registry in our country. 2-3 While Pakistan bears a high burden of vascular diseases, the centres offering state-of-the-art services are limited.4 The lack of accurate statistics makes it more challenging to predict the disease course and its relationship with geography, its complications, and outcomes. Inadequacy of follow-up and poor reporting of patients’ functional status also become barriers to optimal care. The utilisation of a Vascular Registry can gather information regarding all such variables. It makes it possible to analyse data in a large patient population by collecting prospective data routinely.5 This is of great importance in improving the standards of vascular surgery at a national level. Even with long-term follow-up, future studies miss rare incidences and other critical information. However, scientific analysis is more feasible in sufficiently large data sets, such as those found in registries. Such datasets can also be utilised to generate new hypotheses and design more impactful studies.5,6 However, the trend of manual data entry and limited reliance on IT provide a setback to registry development in our country. This adversely affects data quality, and essential information may go missing. There is an intra- and inter-hospital lack of uniformity in reporting, and thus, the development of standardised guidelines becomes pertinent. The digitalisation of information via establishing a national registry will surely aid in this process. This process seems more feasible with the use of computerised national identity cards which are being widely used in patient registrations in major hospitals. Maintaining files in both hard and soft copies is time-consuming until a complete transition to electronic data storage is possible. This calls for taking up the task of computerisation at a rapid pace. A robust software system needs to be used that is user-friendly and poses no threats of security breach. We believe that a collaborative effort by the community’s vascular surgeons to build a national registry will result in data centralisation and help in managing resources and improve the quality of care. –Continue